Antimycobacterial activity of novel hydrazide-hydrazone derivatives with 2H-chromene and coumarin scaffold. Issue 2 (15th January 2017) - Angelova, Violina T.; Valcheva, Violeta; Vassilev, Nikolay G.; Buyukliev, Rosen; Momekov, Georgi; Dimitrov, Ivan; Saso, Luciano; Djukic, Mirjana; Shivachev, Boris
Graphical abstract: Highlights: 22 (16 new) hydrazides-hydrazones were evaluate for antimycobacterial activity. 8 new hydrazides-hydrazones exhibited activity better than isoniazid. 3 hydrazones with favorable selectivity index are promising for further investigations. Structure-activity relationship for this class of compounds has been established. Abstract: This study reports the synthesis of new 2 H -chromene or coumarin based acylhydrazones, which were evaluated for their in vitro antimycobacterial activity against reference strain Mycobacterium tuberculosis H37Rv and compared to the first-line antituberculosis drugs, isoniazid (INH) and ethambutol (EMB). The most active compounds7m (MIC 0.13 μM), 7o (MIC 0.15 μM) and7k (MIC 0.17 μM) demonstrated antimycobacterial activity at submicromolar concentration level and remarkably minimal associated cytotoxicity in the human embryonic kidney cell line HEK-293T. Structure-activity relationship for this class of compounds has been established.